Efektivitas brain qym terhadap penurunan tingkat nyeri pada anak post operasi: Studi kuasi eksperimen di RSUD Meuraxa Banda Aceh - Asniah Syamsuddin; Roma Sitio; Ritawati Ritawati; Nurhayati Nurhayati; Desiana Desiana (Poltekkes Kemenkes Aceh, 2025)
Background: Pain caused by surgical wounds causes discomfort and stress in children, so measures are needed to reduce it. Brain gyms can reduce pain because the movements can increase blood flow and stretch the nerve muscles.Objective: This study aims to determine the effect of brain gym on pain levels during surgical wound care in children.Methods: This study used a quantitative design of the quasi-experimental method with a one-group pre- and post-test without control. This study was conducted in the pediatric room of Meuraxa Hospital Banda Aceh on 22 children undergoing surgical wound care (total sampling) on June 2 – August 30, 2022. The intervention was carried out by playing brain gym videos and asking children to follow the movements in the video when children were treated with surgical wounds. The instrument used the Faces Pain Rating Scale. Data analysis used a paired T test statistical test with a significance level of 0,05 and 95% confidence level.Results: The results of this study showed that the most pain levels before the intervention were at the severe pain level, namely 12 people (54,5%), and the pain level after the intervention was at moderate pain, totaling 16 people (72,8%). The results of the analysis showed a significant difference in pain before and after the brain gym (p<0,05).Conclusion: Brain gym can reduce pain in children who are undergoing surgical wound care.